O CURRÍCULO DA ESCOLA NO HOSPITAL: UMA ANÁLISE DO SERVIÇO DE ATENDIMENTO À REDE DE ESCOLARIZAÇÃO HOSPITALAR- SAREH/PR - Zaias, Elismara (2011)
This research analyses how the hospital school curriculum of the Hospital Schooling Network Service (SAREH/Paraná) is built in three public university hospitals. The aims of this work were the following: a) to understand how the hospital school curriculum is built; b) to describe the SAREH Programme; c) to identify and analyse the organisation of school curriculum in the SAREH hospitals; d) to analyse the pedagogical practices of the schools’ teachers and pedagogues at the SAREH Programme hospitals. The theoretical references for curriculum discussions consisted of ideas from Gimeno Sacristán (1998, 2000, 2002, 2007) and other authors that approach the curriculum theme, such as Coll (1995), Pacheco (2005), and Torres González (2002). Authors who have provided understanding of Hospital Pedagogy were also studied: Barros (1999), Fonseca (2003), Fontes (2003), Matos and Mugiatti (2008, 2009), Paula (2005, 2007). The research methodology was qualitative, more specifically case study, and included the following procedures: a) analysis of the Curriculum and Pedagogical Projects in the SAREH hospitals; b) observations, recorded in field notes, of the pedagogical practices developed by teachers and pedagogues; c) interviews with the person responsible for the idea of the programme and with teachers and pedagogues who take part in it. The main conclusions reached were: teachers develop a discipline-based curriculum, following the State Curriculum Guidelines of Paraná, and use particular strategies that allow them to organise and distribute curriculum contents in such a way that the curriculum is not closed or mechanical, addressing the interests and needs of the hospitalised students. It was observed that the recommendations present in the Curriculum and Pedagogical Projects of the hospitals indicate how the SAREH Programme curriculum is structured, since each teacher reconfigures the curriculum within the hospital context according to their own methodology, concepts, and professional experience. Furthermore, a major improvement could be noted in the way the teams of the SAREH hospitals have systematised the curriculum organisation according to the context. Nonetheless, it became clear that teachers and pedagogues showed the need to build a common curriculum in order to provide the programme with an identity. In that regard, it is worth pointing out the need for constant reflections and discussions on the curriculum organisation for the hospital environment.